Reimagining the approach for advancing maternal health equity through authentic patient engagement and research practices - Sutton, Karey M.; Wyand, Shelby; Char, Chandra A.; McCullers, Asli (Frontiers in Health Services, 2024)
High maternal mortality and morbidity rates continue to significantly impact the United States, with Black birthing individuals being two to three times more likely to die from pregnancy related causes compared to other races. Ongoing discussions are crucial to improving care delivery and amplifying the experiences and needs of marginalized survivors of pregnancy-related psychological harm. Thus, this commentary leverages current literature and vignettes to deliver recommendations on authentically engaging patients in the cross-sectoral process of dismantling harmful clinical and research practices, thus building a safe, equitable future for maternal health.